Biomolecular function discovery through computational protein sequence analysis : project 2 - Neo, Keng Hwee (2009)
Bioinformatics can facilitate protein function discovery. Previous study has predicted the human Zinc-Binding Dehydrogenase domain-containing 2 (ZADH2) cDNA to encode for a novel peroxisomal protein (Kurochkin et al., 2005). Our analysis of its protein sequence agrees with their findings. We inferred the function of the human ZADH2 protein based on sequence similarity with homologus proteins, multiple sequence alignment of homologus proteins, and phylogenetic inference. ZADH2 protein was found to be related to the prostaglandin reductases, quinone oxidoreductases, and alcohol dehydrogenases. These enzymes generally perform reduction-oxidation reactions. ZADH2 protein share a common Nicotinamide Adenine Dinucleotide (Phosphate) (NAD(P))-binding domain with them, and has the active sites, typical of the quinone oxidoreductase family. As such, ZADH2 protein is believed to have antioxidant function in the peroxisome. By comparing with control cells, cells transfected with ZADH2 expression vector have slightly better survival when faced with oxidative stress. There was, however, no difference in both the level of lipid peroxidation and antioxidant capacity.